ANALISIS KINERJA PEMERINTAH KOTA MEDAN DALAM PENANGGULANGAN SAMPAH MELALUI PROGRAM BANK SAMPAH - Ijtihadiyah, Faiza; Sinaga, DM Miranda; ridwan , mohammad; Siregar, Tiara Oktiani; Pasaribu, Angelina Theresia; Mutiara, Pinta (Universitas Cenderawasih, 2025)
The Bank Sampah program was introduced as one of the innovative solutions that involves the community to participate in community-based waste management. The program adopts the 3R principles (reduce, reuse, recycle) and provides economic incentives to increase community awareness and contribution to waste management. This study aims to analyze the effectiveness of the Bank Sampah program in Medan City from the aspects of waste volume reduction, community participation, and its impact on the environment and local economy. This research is important to assess the effectiveness of the program, not merely its implementation. A quantitative method was used with a survey of communities involved in the program. Data were collected through a questionnaire covering aspects of the frequency of waste deposit, the level of knowledge of the community, as well as their perception of the benefits of the program. Data analysis was conducted using statistical software such as SPSS to produce valid and objective findings. The results showed that although the number of active waste banks decreased from 174 to 12 units in 2023, the program was still able to manage around 120 tons of waste per year. Besides helping to create a clean environment, the program also contributes to social activities, such as the prevention of stunting in children. However, challenges to the sustainability of waste bank operations are still significant, such as the low level of public awareness in sorting waste at the household level and the lack of innovative strategies from managers. This study recommends increasing socialization to the community, strengthening collaboration between actors, and developing creative strategies to improve the sustainability of waste banks. The findings are expected to serve as a reference for the government in formulating more effective and sustainable policies to address waste problems in Medan City.